Persuasive Communication in Digital Advertisements for Beauty Salons on the Instagram Account @della.bautybar - Esa Astrid Rhaisa; Nur Elisa; Farida Nurfalah; Welly Wihayati (Journal Of Social Science (JoSS), 2025)
Digital technology and the internet have revolutionized the way businesses operate, allowing them to reach a wider range of targets, increase efficiency, and accelerate growth. The beauty industry, including the beauty salon Della Beautybar, relies heavily on advertising to increase visibility and win customers. The purpose of this study was to analyze the persuasive communication applied by Della Beautybar Beauty Salon through digital advertising on Instagram. The conclusion of this study is that the persuasive communication applied by Della Beautybar can influence the customer's decision to place an order. The methodology of this study is the use of a qualitative approach with data technique analysis in the form of observation, interviews and documentation attachments. The sample of this study is the Instagram post of Della Beautybar, the owner of the Beauty Salon and the respondents who were selected purposively. This research was conducted for 2 months. The results of this study show that the persuasive communication and advertising implemented by Della Beautybar are successful in attracting attention and building customer loyalty. This includes engaging visual content, building customer interest with promotions and testimonials, providing superior service through quality, and making decisions with easy access to reservations. The recommendation from this study is that Della Beautybar needs to continue to improve the quality of visuals and information conveyed through Instagram, as well as improve interaction with customers to maintain customer trust and loyalty.